(untitled) (Nepal Agriculture Research Journal, 2009)
Hiunde (Boro) rice has not been popularized due to least attention given to this crop in Nepal. In order to estimate the production function of this crop, a field survey in Morang district during 2002/2003 was carried out using a semi-structured questionnaire. The primary information was collected through face to face interview. The result of the empirical model of Cobb-Douglas production function revealed the model significant at 1% level and defined 95% variation in Hiunde rice production due to variation in independent variables included in the model. The coefficient of area, nitrogen, phosphorous, and tractor hour were found significant at 1% level while the dummy for more than 10 times of irrigation was significant at 5% level and up to 10 times of irrigation and potash was significant at 10% level. The effect of human and bullock labor was found non-significant. Among the sampled farmers the average cropping intensity was 194% and average yield of Hiunde rice was 4802.50 kg/ha. On an average 131 kg of nitrogen, phosphorous and potash was applied for one ha and 15 irrigations in average. The net benefit from Hiunde rice was found to be Rs. 14507.41/ha with 1.73 benefit cost ratio. About 31% cost was incurred in land preparation and transplanting which was highest among the operations. It was followed by the costs incurred in fertilizers and agrochemicals which counted 23%. Key words: Estimate; Hiunde rice; production function DOI: 10.3126/narj.v7i0.1874 Nepal Agriculture Research Journal Vol.7 2006 pp.88-97